2004
DOI: 10.1007/s11669-004-0003-2
|View full text |Cite
|
Sign up to set email alerts
|

(Sn-Ag)eut+Cu soldering materials, part I: Wettability studies

Abstract: The maximum bubble pressure, dilatometric, and meniscographic methods were used in investigations of the surface tension, density, wetting time, wetting force, contact angles, and interfacial tension of liquid (Sn-Ag) eut and two (Sn-Ag) eut + Cu alloys (Cu at.% = 0.46 and 0.74). The density and surface tension measurements were conducted in the temperature range from 230 to 950°C, and the meniscographic investigations were carried out at 252°C. The resultant values of surface tension were compared with those … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 14 publications
0
31
0
1
Order By: Relevance
“…4 and their elaborated linear equations are presented in Table 3 fig. 4. temperature dependences of the surface tension for the (AgSn)eut +Zn liquid alloys.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…4 and their elaborated linear equations are presented in Table 3 fig. 4. temperature dependences of the surface tension for the (AgSn)eut +Zn liquid alloys.…”
Section: Resultsmentioning
confidence: 99%
“…The determination of the density was conducted with the use of the mentioned below relation: (4) where: r is the density, m is the mass of the metal or alloy, d is the crucible diameter and h is the height of the metal or alloy in the crucible.…”
Section: Density Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Table 1 there are summarized the updated investigated systems with references: (Gąsior, Moser & Pstruś, 2001); (Moser, Gąsior & Pstruś, 2001a); (Moser, Gąsior, Pstruś, Zakulski, Ohnuma,. Liu et al, 2001c); (Moser, Gąsior & Pstruś, 2001b); (Gąsior, Moser, & Pstruś, 2003a); (Moser, Gąsior, Ishida, Ohnuma, Liu, Bukat et al, 2005b); (Pamies, Garcia-Cordovilla & Louis, 1984) (Nogi, Oishi & Ogino, 1989); (Gąsior, Moser & Dębski, 2004c); (Liu, Inohana, Ohnuma, Kainuma, Ishida, Moseret al, 2002); (Gąsior, Moser, Pstruś, Krzyżak & Fitzner, 2003b); ; (Moser, Gąsior & Pstruś, 2005a); (Gąsior, Moser, Pstruś, Bukat, Kisiel & Sitek, 2004e); (Moser, Gąsior, Pstruś & Księżarek, 2002); (Moser, Gąsior, Pstruś, Ishihara, Liu, Ohnuma et al, 2004d); (Gąsior, Moser & Pstruś, 2004b); (Moser, Gąsior, Ishida, Ohnuma, Bukat, Pstruś et al, 2004c); (Gąsior, Moser, Bukat, Pstrus, Sitek, & Kisiel, 2004d); (Kisiel, Gąsior, Moser, Pstruś, Bukat & Sitek, 2005). (Gąsior et al, 2001) Pb -Sn (Gąsior et al, 2001) (Sn-Ag) eut +Zn * Sn (Moser et al, 2001a) Ag -Sn (Moser et al, 2001a) (Sn-Ag) eut +In (Liu et al, 2002) In (Moser et al, 2001c) Ag -In (Moser et al, 2001c) (Sn-Ag) eut +Bi (Moser et al, 2001b) Ag (Moser et al, 2001c) Bi -Sn ) (Moser et al, 2001b) (Sn-Ag) eut +Cu (Gąsior et al, 2004e) ) Bi (Moser et al, 2001b) In -Sn (Liu et al, 2002) (Sn-Ag) eut +Sb Sb (Gąsior et al, 2003a) Ag -Bi …”
Section: Introductionunclassified
“…The wetting balance test can be used to observe the dynamic process of wetting by measuring the force that acts between the immersed specimen and the molten solder. In a recent publication on addition of Cu to binary eutectic Sn-Ag (Gąsior et al, 2004e), we reported the joint results with industrial institutes dealing with the production and testing of Pb-free solders to combine data of the surface tension from measurements in a protective atmosphere with the results from meniscographic studies. This was possible using two different meniscographs and performing measurements on wetted and not wetted specimens in air.…”
Section: Introductionmentioning
confidence: 99%